Sintering and electrical behavior of ZrP 2 O 7 –CeP 2 O 7 solid solutions Zr 1-x Ce x P 2 O 7 ; x = 0–0.2 and (Zr 0.92 Y 0.08 ) 1-y Ce y P 2 O 7 ; y = 0–0.1 for application as electrolyte in intermediate temperature fuel cells - Gautam S.K.; Singh A.; Mathur L.; Devi N.; Singh R.K.; Song S.-J.; Henkensmeier D.; Singh B. (My University, 2025)
ZrP 2 O 7 -CeP 2 O 7 solid solutions, Zr 1-x Ce x P 2 O 7 ; x = 0–0.2 and (Zr 0.92 Y 0.08 ) 1-y Ce y P 2 O 7 ; y = 0–0.1, were prepared by partially replacing Zr 4+ with Ce 4+ and its effect on the phase composition, sintering behavior, microstructure, and ionic conductivity is analyzed. Ce 4+ -doped specimens showed improved sintering behavior due to the partial reduction of Ce 4+ to Ce 3+ , as confirmed by X-ray photoelectron spectroscopy (XPS). In unhumidified atmosphere, the electrical conductivity of Zr 1-x Ce x P 2 O 7 increased with increasing cerium content, which can be attributed to the increase in densification and formation of oxygen vacancies due to the partial reduction of Ce 4+ to Ce 3+ . For (Zr 0.92 Y 0.08 ) 1-y Ce y P 2 O 7 ; y = 0–0.1 specimens, the electrical conductivity increased ≥ 4 orders of magnitude during humidification in air (pH2O = 0.12 atm). At 80 °C, specimen (Zr 0.92 Y 0.08 ) 0.9 Ce 0.1 P 2 O 7 (ZYCP10) showed a maximum of 1.72 × 10 −2  S cm −1 which decreased sharply at 100 °C. Furthermore, Zr 0.92 Y 0.08 P 2 O 7 (ZYP), (Zr 0.92 Y 0.08 ) 0.95 Ce 0.05 P 2 O 7 (ZYCP5), and ZYCP10 specimens humidified at 160 °C showed the maximum conductivity of 1.04 × 10 −3 , 1.32 × 10 −3 , and 8.09 × 10 −3 S cm −1 , respectively, at 190 °C. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.